Reconstruction of a continuous high-resolution CO 2 record over the past 20 million years - Van De Wal, R. S.W.; De Boer, B.; Lourens, L. J.; Köhler, P.; Bintanja, R. (Climate of the Past, 2011)
The gradual cooling of the climate during the Cenozoic has generally been attributed to a decrease in CO 2 concentration in the atmosphere. The lack of transient climate models and, in particular, the lack of high-resolution proxy records of CO 2 , beyond the ice-core record prohibit, however, a full understanding of, for example, the inception of the Northern Hemisphere glaciation and mid-Pleistocene transition. Here we elaborate on an inverse modelling technique to reconstruct a continuous CO 2 series over the past 20 million year (Myr), by decomposing the global deep-sea benthic δ 18 O record into a mutually consistent temperature and sea level record, using a set of 1-D models of the major Northern and Southern Hemisphere ice sheets. We subsequently compared the modelled temperature record with ice core and proxy-derived CO 2 data to create a continuous CO 2 reconstruction over the past 20 Myr. Results show a gradual decline from 450 ppmv around 15 Myr ago to 225 ppmv for mean conditions of the glacial-interglacial cycles of the last 1 Myr, coinciding with a gradual cooling of the global surface temperature of 10 K. Between 13 to 3 Myr ago there is no long-term sea level variation caused by ice-volume changes. We find no evidence of change in the long-term relation between temperature change and CO 2 , other than the effect following the saturation of the absorption bands for CO 2 . The reconstructed CO 2 record shows that the Northern Hemisphere glaciation starts once the long-term average CO 2 concentration drops below 265 ppmv after a period of strong decrease in CO 2 . Finally, only a small long-term decline of 23 ppmv is found during the mid-Pleistocene transition, constraining theories on this major transition in the climate system. The approach is not accurate enough to revise current ideas about climate sensitivity.